THE SYRIAN CRISES AND NON-COMBATANT CASUALTIES: CONTEMPLATIONS ON THE HUMANITARIAN DIMENSIONS OF A JUST WAR - Nnenna, Adeline; Idike, A. (European Scientific Journal, ESJ, 2014)
The general objective of this paper is to utilize the just war theoretical framework in examining the implications of the Syrian crisis on women and children. The specific objectives therefore, are to (i) study the extent to which Syrian women and children have been adversely affected by the Syrian crisis and (ii) sensitize the international community on the avoidable indignities and inhumanities suffered by vulnerable women and children, during escalated intra-state conflicts. In the final analysis, opines the paper, a just war must minimize the incidence of noncombatant causalities, particularly women and children. This is the challenge of the international community in the Syrian crisis.